Antigenic determinants of the attachment protein of Mycoplasma pneumoniae shared by other pathogenic Mycoplasma species. - Clyde, W A (1986)
In previous studies with hyperimmune rabbit antisera, we found evidence of serologic cross-reactivity among Mycoplasma pneumoniae, Mycoplasma genitalium, and Mycoplasma gallisepticum. Because of certain biologic and morphologic similarities of these species, attempts were made to determine if this cross-reactivity related to the attachment protein (P1) of M. pneumoniae. Monoclonal and monospecific antibodies against P1 were used to probe proteins of the other species by immunoblotting. One of the P1 monoclonal antibodies was reactive with a smaller protein of M. genitalium; rabbit antiserum raised by immunization with P1 excised from a sodium dodecyl sulfate-polyacrylamide gel electrophoresis gel was found to react with a similar-sized protein of M. gallisepticum. These preliminary findings suggest antigenic sharing among the species examined; however, limitations of the methods used are discussed.